The Impact of Intraoperative Position Changes on Hemodynamics and Cardiac Electrophysiological Balance Index in Patients with Severe Obesity Undergoing Laparoscopic Sleeve Gastrectomy - Celik, Fatma; Dagli, Recai; Aksu, Ahmet; Harman, Murat; Bolat, Esef; Demirel, Ismail; Altun, Aysun Yildiz (Springer, 2026)
Background Pneumoperitoneum and the reverse Trendelenburg (RT) position during laparoscopic sleeve gastrectomy (LSG) can induce autonomic instability and increase the risk of arrhythmias by reducing venous return. This study aimed to evaluate the impact of surgical positioning during LSG on autonomic cardiac function, using hemodynamic parameters and the cardiac electrophysiological balance index (iCEB = QT/QRS) as a biomarker. Methods This prospective observational study included 66 patients with severe obesity who underwent LSG. Measurements were recorded at five distinct time points, corresponding to specific patient positioning during the procedure: P-baseline (before induction, supine), P1 (after induction, supine), P2 (after pneumoperitoneum, supine), P3 (during pneumoperitoneum, RT), and P4 (after desufflation, RT). Results Systolic, diastolic, and mean arterial pressures (SAP, DAP, and MAP) significantly decreased at all positions compared to baseline (p < 0.001 for each). Compared to post-induction (P1), SAP values were substantially higher in the P2 and P4 positions (p < 0.05, p < 0.001, respectively). Heart rate significantly decreased at P1 compared to baseline (p < 0.004) and subsequently increased at P2 and P3 relative to P1 (p < 0.001 and p < 0.009, respectively). A notable increase in iCEB was observed at P4 when compared to P1, P2, and P3 (p < 0.003, p < 0.001, and p < 0.021, respectively). Despite these changes, iCEB values remained within the reference range across all measured positions. Conclusion Despite the observed effects of positional changes and pneumoperitoneum on hemodynamic and cardiac electrical parameters during LSG, most patients tolerated these changes well. Crucially, iCEB values remained within the normal reference range throughout the procedure, indicating preserved cardiac autonomic regulation.
Keywords: Laparoscopic sleeve gastrectomy; Severe obesity; Pneumoperitoneum; Patient positioning; Electrocardiography; Hemodynamics